GEMSHiDa Apps: Explore Hindu-Buddha History Materials with an Android Game for Social Studies Students in Junior High School - Mey Lafaiza Sukmaning Haresa; Bayu Kurniawan; Mohamed Jefferi bin Haji Mat Lazim (Indonesian Journal of Social Science Education (IJSSE), 2024)
One potential learning tool for engaging students in play while providing comprehensive information on Hindu-Buddhist content is an educational game. This study focuses on developing the GEMSHiDa app, an educational game centered on Hindu-Buddhist history for Android devices, intended for social studies students in Junior Hight School. Following a research and development (R&D) approach using the ADDIE model, validation from two experts rated the app's teaching material as "Very Good." Additionally, feedback on the app's design and accessibility was deemed "Good" by other validators. Furthermore, classroom testing of the GEMSHiDa app yielded a "Very Good" rating, indicating its suitability for social studies instruction in middle schools.